3 QUESTIONS ABOUT: CARA BLACK'S AIMÉE LEDUC SERIES. - OTT, BILL (Booklist, 2019)
An interview with the author Cara Black is presented. Topics include launch of her beloved Aimée Leduc series with "Murder in the Marais," how authors of mystery series deal with the passing of time in all sorts of ways, and book series on a kind of domestic drama that develops alongside the mystery element.